PENGARUH PENGGUNAAN APLIKASI BUSUU SEBAGAI MEDIA PEMBELAJARAN TERHADAP PENGUASAAN MUFRODAT - Yulia Wulanda Putri; Muhammad Syaifullah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2026)
This study aims to determine the effect of using the Busuu application on the Arabic vocabulary mastery of Grade X students at MA Roudhotut Tholibin. A quasi-experimental method with a non-equivalent control group design was employed. The study sample consisted of 29 students selected via purposive sampling, divided into experimental and control groups. Data were collected using pretest and posttest instruments and subsequently analyzed using the Independent Samples T-test and N-Gain Score analysis via SPSS. The Independent Samples T-test results revealed a statistically significant difference between the two groups, evidenced by a calculated t-value of 8.089 (df = 27) and a Sig. (2-tailed) value of 0.000 (< 0.05). Based on the analysis of effectiveness, the experimental class using the Busuu application achieved an average N-Gain Score of 54.86% (categorized as